Granulocytic Myeloid-Derived Suppressor Cells as Negative Regulators of Anticancer Immunity - Kramer, Elliot D.; Abrams, Scott I. (Frontiers in Immunology, 2020)
The immune system plays a critical role in cancer progression and response to therapy. However, the immune system can be compromised during the neoplastic process. Notably, the myeloid lineage, which gives rise to granulocytic cells, including neutrophils, is a well-recognized target of tumor-mediated immune suppression. Ordinarily, granulocytic cells are integral for host defense, but in neoplasia the normal process of granulocyte differentiation (i.e., granulopoiesis) can be impaired leading instead to the formation of granulocytic (or PMN)-myeloid-derived suppressor cells (MDSCs). Such cells comprise various stages of myeloid differentiation and are defined functionally by their highly pro-tumorigenic and immune suppressive activities. Thus, considerable interest has been devoted to impeding the negative contributions of PMN-MDSCs to the antitumor response. Understanding their biology has the potential to unveil novel therapeutic opportunities to hamper PMN-MDSC production in the bone marrow, their mobilization, or their effector functions within the tumor microenvironment and, therefore, bolster anticancer therapies that require a competent myeloid compartment. In this review, we will highlight mechanisms by which the neoplastic process skews granulopoiesis to produce PMN-MDSCs, summarize mechanisms by which they execute their pro-tumorigenic activities and, lastly, underscore strategies to obstruct their role as negative regulators of antitumor immunity.